Stochastic epidemiological model: Simulations of the SARS-CoV-2 spreading in Mexico - Pablo Carlos López Vázquez; Gilberto Sánchez González; Jorge Martínez Ortega; Renato Salomón Arroyo Duarte (PLoS ONE, 2022)
In this paper we model the spreading of the SARS-CoV-2 in Mexico by introducing a new stochastic approximation constructed from first principles, where the number of new infected individuals caused by a single infectious individual per unit time (a day), is a random variable of a time-dependent Poisson distribution. The model, structured on the basis of a Latent-Infectious-(Recovered or Deceased) (LI(RD)) compartmental approximation together with a modulation of the mean number of new infections (the Poisson parameters), provides a good tool to study theoretical and real scenarios.